O postal em seus movimentos: comunicação e memória - Sotilo, Caroline Paschoal (2009)
This is a research on post cards reflection as an iconographic source, contemplating its relation with photography and its popularization, interconnecting questions from an era of the multiplied imaging for mass consumption, and at the same time generating a new graphic, editorial and photographic working market, With the advent of the post card and, simultaneously, the emerging of illustrated magazines, as well as other forms of diffusion of printed image, especially the photographic image, it represented a true revolution on history of culture (Kossoy). A support we can consider as an important publicizer of the photographic image, and moreover, one of the democratizer 2 of that image, in the turn of the 19th to the 20th century. Further, it increases to the corpus of the reseach by its relation to the city, its representations and repertoires, as well as a vehicle of correspondence, registry of an epoch, of sociais plans, ideologies construction, imageries development. The post card reminds us, thus, of the printed recollection and the industrial period this support is associated with. This reseach intends to analyze post cards while contribution to a special type of memory in our culture ( public and private, a living and current document) and their approachable extensions